Unsupervised but not supervised gait parameters are related to fatigue in Parkinson’s disease: a pilot study - Pilotto, Andrea; Rizzardi, Andrea; Zatti, Cinzia; Hansen, Clint; Donini, Antonio; Romijnders, Robbin; Maetzler, Walter; Padovani, Alessandro (Frontiers in Aging Neuroscience, 2023)
Introduction Fatigue is a common and disabling symptom in Parkinson’s disease (PD), also affecting gait. Detection of fatigue-associated changes of gait using mobile health technologies (MHT) could become increasingly effective. Methods Cognitively unimpaired PD patients without fluctuations (UPDRS IV < 1) underwent a standard neurological assessment including the PD-Fatigue scale (PFS-16). PD patients with (PD-F) and without fatigue (PD-N) were matched for age, sex, cognitive function and disease severity. Each participant underwent MHT gait assessment under supervised condition (SC) and unsupervised condition (UC). Results Gait parameters of 21 PD-F and 21 PD-N did not significantly differ under SC. Under UC, PD-F showed higher step time, step time variability and asymmetry index compared to PD-N and the PFS-16 correlated with step time. Conclusion This is the first MHT-based study with PD patients showing a correlation between fatigue and gait parameters. In addition, the data collected suggest that UC is clearly superior to SC in addressing this question.